KAJIAN PENGENDALIAN PENYAKIT BUSUK PANGKAL BATANG LADA DENGAN MODIFIKASI IKLIM MIKRO - Agus Salim (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2017)
Study of Pepper Rot Stem Disease Controlling With Micro Climate Modification. Pepper stem rot disease Phytophthora capsici Leon is a major disease on pepper plants in the Southeast Sulawesi areas. The control of this fungus disease is difficult because it goes in the trunk network and it can be known after the plants wilt. The purpose of this study was to determine the microclimate that could hinder the development of the fungus P. capsici.This study was conducted in Konawe South, Southeast Sulawesi from February to November 2015. The study used randomized block design with treatments tested were 1) Control; 2) Solar irradiation between 25-30%; 3) Solar irradiation between 50-55% and 4) Irradiation between 75-80%. Each treatment was repeated 5 times. The parameters observed were soil moisture, the intensity of the irradiation, the percentage of attacks and severity of disease levels and productivity. Research results indicated that the modification of solar radiation affected the air humidity, so that the development of stem rot disease pepper could be controlled. On irradiation of 50-55% can reduce the severity of an attack up to 77.36%.diseases, controlling, climate, pepper ABSTRAKPenyakit busuk pangkal batang lada Phytophthora capsici Leon, merupakan penyakit utama pada tanaman lada di Sulawesi Tenggara. Pengendalian penyakit cendawan ini masih sulit karena masuk dalam jaringan batang dan diketahui setelah tanamannya layu. Tujuan penelitian ini untuk mengetahui iklim mikro yang dapat menghambat perkembangan cendawan P. capsici. Penelitian ini dilaksanakan di Kabupaten Konawe Selatan, Sulawesi Tenggara dari bulan Februari sampai Nopember 2015. Penelitian menggunakan Rancangan Acak Kelompok dengan perlakuan yang dicobakan adalah: 1) Kontrol; 2) Penyinaran matahari antara 25 – 30%; 3) Penyinaran matahari antara 50 – 55%, dan 4) Penyinaran antara 75 – 80%. Setiap perlakuan diulang sebanyak 5 kali. Parameter yang diamati meliputi kelembaban tanah, intensitas penyinaran, persentase serangan dan tingkat keparahan serangan penyakit serta produktivitas. Hasil penelitian menunjukkan bahwa modifikasi penyinaran matahari mempengarhi kelembaban udara, sehingga perkembangan penyakit busuk pangkal batang lada dapat ditekan. Pada penyinaran 50 – 55% dapat menekan tingkat keparahan serangan sampai 77,36%.penyakit, pengendalian, iklim, lada